Masa Depan Indusrialisasi dalam Mengahadapi Transfomer Teknologi dan Tantangan Ekonomi Global di Era Digital - Adrian Firmansyah; Aisah Nurul Ainun; Muhammad Yasin (Indo Publishing, 2026)
Industrialization is a key pillar of economic development, playing a crucial role in increasing productivity, creating jobs, and driving economic growth. The rapid development of digital technology has transformed production, distribution, and consumption patterns in the industrial sector. Furthermore, economic globalization has intensified competition between countries. This article aims to analyze the future of industrialization in the face of technological transformation and the challenges of the global economy in the digital era. The method used is a literature review, reviewing various literature, journals, and reports related to industrialization and the development of digital technology. The study shows that the application of technologies such as artificial intelligence (AI), the Internet of Things (IoT), big data, and automation can improve industrial efficiency and competitiveness. However, this transformation also poses challenges in the form of changing workforce needs, the digital divide, and increased global competition. Therefore, a strategy focused on human resource development, technological innovation, and adaptive industrial policies is needed so that industrialization can optimally contribute to sustainable economic development.